2022
DOI: 10.1002/chem.202202157
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Assembly of Interacting Enzymes Yields Highly‐Active Nanoparticles for Flow Biocatalysis

Abstract: All-enzyme hydrogel (AEH) particles with a hydrodynamic diameter of up to 120 nm were produced intracellularly with an Escherichia coli-based in vivo system. The inCell-AEH nanoparticles were generated from polycistronic vectors enabling simultaneous expression of two interacting enzymes, the Lactobacillus brevis alcohol dehydrogenase (ADH) and the Bacillus subtilis glucose-1-dehydrogenase (GDH), fused with a SpyCatcher or SpyTag, respectively. Formation of inCell-AEH was analyzed by dynamic light scattering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…To gain detailed insight into the mechanisms of nanoscale enzyme cascades, the components involved were precisely quantified and extensively characterized. The investigation of the kinetic parameters of the individually immobilized biocatalysts of the cascade is particularly important, as it was known from previous studies that DON immobilization of individual KREDs can lead to significantly altered enzymatic activity, [ 46 ] and that the increase in activity of one enzyme should increase the productivity of the entire cascade. [ 27 ] Therefore, both cascade enzymes were first examined individually with respect to their kinetic parameters on the microbeads and DNA origami before analyzing the activity of the co‐assembled cascade.…”
Section: Resultsmentioning
confidence: 99%
“…To gain detailed insight into the mechanisms of nanoscale enzyme cascades, the components involved were precisely quantified and extensively characterized. The investigation of the kinetic parameters of the individually immobilized biocatalysts of the cascade is particularly important, as it was known from previous studies that DON immobilization of individual KREDs can lead to significantly altered enzymatic activity, [ 46 ] and that the increase in activity of one enzyme should increase the productivity of the entire cascade. [ 27 ] Therefore, both cascade enzymes were first examined individually with respect to their kinetic parameters on the microbeads and DNA origami before analyzing the activity of the co‐assembled cascade.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Later work indicated that AEH can be produced by genetically programmable selfassembly of arbitrary enzymes, [15][16][17][18] however, monolithic AEH materials have some limitations in terms of diffusion and mass transport within the materials, calling for improved formulations of these powerful biocatalysts. [19] In order to simultaneously maintain the solid anchorage and high enzyme concentration of AEH while still realizing a high surface-to-volume ratio for efficient perfusion and mass transport, we reasoned that these two aspects could be reconciled by foam formulations of AEH. Liquid foams consist of gas bubbles densely packed in a liquid carrier matrix to form a network of gas/liquid interfaces in which merging of the bubbles is prevented by the addition of stabilizing agents such as low molecular weight surfactants, polymers, proteins, nanoparticles or mixtures thereof.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Later work indicated that AEH can be produced by genetically programmable self‐assembly of arbitrary enzymes, [ 15–18 ] however, monolithic AEH materials have some limitations in terms of diffusion and mass transport within the materials, calling for improved formulations of these powerful biocatalysts. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%